Optimalisasi Desain Pembelajaran PAI Kelas XI SMA Pelita Raya Jambi - Aris Munandar; Rahmadea Novriana; Anisa Arda; Fitria Ramadhani; Indo Safna; Tsaniyah Zahroh Rohimah (Syntax Corporation Indonesia, 2024)
There are many problematic facts about students in the learning process. Teachers or teaching staff also tend to be less than optimal in developing teaching methods and media used in delivering learning resources. This has an impact on the aim of this research is to understand student problems, student learning styles and Islamic boarding school learning methods for class XI at Pelita Raya Jambi private high school. The method used in this research is a qualitative method, specifically case study. The number of informants taken was 31 people. Data collection tools for this research are descriptive questionnaires, observations, interviews and literature studies. The research results show that the teacher's learning methods do not match the students' learning styles. Teachers apply monotonous learning methods, tend to lecture in one direction and experience difficulties in teaching. Meanwhile, 55% of students have a visual learning style, 16% kinesthetic and 29% auditory. This has an impact on 60% of students in the class having difficulty focusing on the material because they are sleepy, bored and more interested in paying attention to their respective gadgets rather than paying attention to the material being explained. Therefore, to optimize learning designs in the future, teachers need this research to serve as a basis for transforming learning designs.